BIG DATA AND ITS ROLE IN THE DIGITAL ECONOMY - Umar Muminovich Asrayev (Ecomind Press, 2025)
Big Data has become a fundamental driver of digital economic transformation, influencing decision-making processes, business strategies, and financial innovations. In Uzbekistan, the adoption of Big Data is gradually expanding across various sectors, including finance, e-commerce, and public administration. This paper explores the role of Big Data in the digital economy, emphasizing its impact on economic growth, financial management, and business optimization. The study examines the opportunities and challenges associated with Big Data implementation, such as data security, infrastructure limitations, and regulatory frameworks. By analyzing international experiences and their applicability to Uzbekistan, this research provides insights into the strategic development of Big Data-driven economic models. The findings highlight the necessity of enhanced digital literacy, data-driven policies, and investment in data analytics infrastructure to maximize the benefits of Big Data in the country’s economic landscape.